A Review on Islamic Social Finance: VosViewer Application - Aam; Aisyah As-Salafiyah (SMART Insight, 2021)
Islamic social finance is one of the Islamic economic instruments considered the right solution to simultaneously achieve social and financial goals. Over time, Islamic social finance has a social role and can be developed in empowering commercial businesses, and its management institutions also become financially efficient and professional industries. This study aims to determine Islamic social finance research trends published by leading journals on Islamic financial economics. The data analyzed consisted of 391 indexed research publications. The data is then processed and analyzed using the VoS viewer application to discover the bibliometric map of Islamic social finance research development. This study found that Islamic social finance has an essential role in contributing significantly to society's economic and social sectors.